2020
DOI: 10.3389/fonc.2020.00769
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated m6A-Related Regulators Are Associated With Tumor Metastasis and Poor Prognosis in Osteosarcoma

Abstract: Background: Osteosarcoma (OS) is the most common primary bone tumor. The disease has a poor prognosis due to the delay in the diagnosis and the development of metastasis. N6-Methyladenosine (m6A)-related regulators play an essential role in various tumors. In this study, a comprehensive analysis was conducted to elucidate the relationship between the expression profiles of m6A-related molecules and the clinical outcome of OS patients. Materials and Methods: Public genome datasets and a tissue microarray (TMA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
54
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 52 publications
4
54
1
Order By: Relevance
“…These results suggested that although FTO was highly expressed in glioma tissues, it might play a protective role for patients with gliomas. Li J. et al (2020) found that the expression of m6A regulators was dysregulated in osteosarcoma, and low expression of FTO and high expression of YTHDF3 was associated with poor prognosis, which was consistent with our findings. Besides, FTO could suppress the self-renewal of ovarian cancer stem cells via inhibiting cyclic adenosine monophosphate (cAMP) signaling pathway ( Huang et al, 2020b ).…”
Section: Discussionsupporting
confidence: 92%
“…These results suggested that although FTO was highly expressed in glioma tissues, it might play a protective role for patients with gliomas. Li J. et al (2020) found that the expression of m6A regulators was dysregulated in osteosarcoma, and low expression of FTO and high expression of YTHDF3 was associated with poor prognosis, which was consistent with our findings. Besides, FTO could suppress the self-renewal of ovarian cancer stem cells via inhibiting cyclic adenosine monophosphate (cAMP) signaling pathway ( Huang et al, 2020b ).…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies have shown that m 6 A methylation modifying enzymes are abnormally expressed in some malignant tumors. Li et al, 18 found that in OS patients, especially in metastatic tissues, disorders involving m6A-related regulatory factors, such as the low expression of METTL3 and METTL14, can be related to poor prognosis of patients. This observation is consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have found that COL1A1 polymorphism is associated with risks of OS transfer and patient death in which COL1A1 polymorphism at rs1061970 has value for overall survival in Chinese OS patients [32] . Research by Li et al found that high expression of HNRNPA2B1 is associated with poor prognosis of OS, and Cox regression analysis showed that HNRNPA2B1 is an independent risk factor for OS [33] . But in our study, the expression level of HNRNPA2B1 does not shown the signi cantly correlated with overall survival in patients with osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%